Kesadaran Hukum Dalam Menafkahi Anak Pasca Putusan Pengadilan - Pahutar, Agus Anwar (IAIN Padangsidimpuan, 2019)
This paper talks about how the legal awareness of parents (fathers) in providing children after the divorce between Father and Mother in the Religious Court until the child is an adult. From the results of the study found facts in the field that the income or expenditure of children after the divorce between Father and Mother is not carried out effectively and continuously. There are several reasons that arise from my father so that he does not fulfill his obligations in accordance with the order of the decision and the applicable law. Therefore if viewed from the indicator of legal awareness, namely the perspective of the pattern of legal behavior of the husband (father), that the father has not had sufficient legal awareness or legal obedience and is still low, even though they know that giving a child to adulthood or age 21 years is mandatory.Â